Influencing Factors and Prevalence of Anxiety in Medical Students: A Cross-Sectional Study - Huong Thi Nguyen; Yen Thi Hoai Phan; Anh-Vu Nguyen-Hoang; Tri-Bao Nguyen; Gia-Phuoc Tran-Thien (Journal of Public Health and Pharmacy)
Introduction: While current research highlights student anxiety globally, limited data exists on the specific situation of Vietnamese medical students. This study addresses this gap by investigating the prevalence and contributing factors of anxiety within this population, aiming to gain a deeper understanding of their mental health experiences.